Cytotoxic Effect of Paclitaxel and Lapatinib Co-Delivered in Polylactide-co-Poly(ethylene glycol) Micelles on HER-2-Negative Breast Cancer Cells - Alicja Zajdel; Adam Wilczok; Katarzyna Jelonek; Monika Musiał-Kulik; Aleksander Foryś; Suming Li; Janusz Kasperczyk (MDPI AG, 2019)
To find better strategies to enhance the cytotoxic effect of paclitaxel (PTX) and lapatinib (LAP) against breast cancer cells, we analyzed the efficacy of a novel delivery system containing polylactide-co-poly(ethylene glycol) (PLA-PEG) filomicelles of over 100 nm in length and spherical micelles of approximately 20 nm in diameter. The 1H NMR measurements confirmed the incorporation of PTX and LAP into micelles. Analysis of the drug release mechanism revealed the diffusion-controlled release of LAP and anomalous transport of PTX. Drug content analysis in lyophilized micelles and micellar solution showed their good storage stability for at least 6 weeks. Blank micelles, LAP-loaded micelles and free LAP did not affect MCF-7 breast cancer cell proliferation, suggesting that the cytotoxicity of PTX-, PTX/LAP-loaded micelles, and the binary mixture of free PTX and LAP was solely caused by PTX. PTX/LAP-loaded micelles showed greater toxicity compared to the binary mixture of PTX and LAP after 48 h and 72 h. Only free PTX alone induced P-gp activity. This study showed the feasibility of using a LAP and PTX combination to overcome MDR in MCF-7 cells, particularly when co-loaded into micelles. We suggest that PTX/LAP micelles can be applicable not only for the therapy of HER-2-positive, but also HER-2-negative breast cancers.